Understanding the European Union : a concise introduction - McCormick, John, 1954- (Houndmills, Basingstoke, Hampshire ; New York : Palgrave Macmillan, 2011)
"This best-selling textbook provides a broad-ranging but concise introduction to the EU, covering all major aspects of European integration. The revised and updated new edition takes full acount of the Lisbon Treaty and the consequences for Europe of the global economic crisis"--Provided by publisher.
What is the European Union? -- The Idea of Europe -- The Evolution of the EU -- The European Institutions -- The EU and its Citizens -- The EU Policy Process -- Economic Policy -- Managing Resources-- The EU and the World.
Includes bibliographical references and index.
Keywords: European Union -- Textbooks